Death and maturity in Le cri des oiseaux fous de Dany Laferrière (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
Through a perspective that is deeply rooted in Haitian tradition, culture, religion and politics, Le Cri des oiseaux fous (2000) by Dany Laferrière (1953-) re-writes the myth of Antigone by narrating the last 24 hours the protagonist spends in Haiti between the announcement of a fellow journalist’s death and the beginning of his own life abroad. The protagonist’s wanderings correspond to a reflection challenging his own identity, especially in the light of his own father’s life and death. In this novel, the narrator’s grief may not directly challenge the dictatorship, but it triggers an evolution to a new maturity and to adult life in a foreign country. The novel is thus readable through the literary genre of the Bildungsroman, and not only as a way to overcome the existential experience of death.
Keywords: Laferrière; death; Bildungsroman; grief; dictatorship; Haiti